Pembinaan Pelatihan Pembukuan Laporan Keuangan Terhadap Wajib Pajak UMKM Di Jakarta - Aji Prasetyo; Endro Andayani; Mohammad Sofyan (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2020)
Coaching training in making corporate financial reports is very important for MSME taxpayers because from the company's financial reports can monitor or see the extent to which the company is making profits, company performance, control of the flow of funds within the company, the values ??of company assets, the value of company liquidity. , as well as the ability to handle all accounts receivable responsibilities. However, there are still many MSMEs that feel they do not need accounting information because it is considered difficult and all the limitations they have. This has an impact on tax reports that can affect state income. This socialization was carried out through Community Service activities. In this Community Service activity, MSMEs players are given simple financial accounting material, insight into the importance of financial accounting for tax reporting, provide motivation for compliance in carrying out tax obligations, and financial accounting training. The PKM results show an increase in knowledge about the principles of bookkeeping for MSMEs and an awareness that bookkeeping is very easy.